The silent voices of the migrant domestic workers in the South African metropolitan: An exploratory study - Motsoeneng, Molefi (Technium Social Sciences Journal, 2021)
The study’s aim is explore the abuse of illegal migrant domestic workers from Lesotho nationals who do domestic work in the South African metropolitan. The women cross the border to escape poverty back home and to search for better lives for themselves and their families in a better-off neighbouring country. Although this may be beneficial for their families, the female migrants are vulnerable to exploitation. The respondents in this study were 10 migrant domestic who are Lesotho nationals working in South Africa metropolitan illegally without a valid work permits. They participated in interview process on their experiences of working as illegal migrant domestic workers in the South African city. The thematic content analysis revealed the following themes: exploitation, humiliation, physical and verbal abuse and sexual harassment. They reported because they are desperate for job they have no choice but to accept the treatment A proposed mitigation of the abuse is extending the Labour Relations Act of 1995, as amended, to include migrant domestic workers, which should enable them to report infringements of this and related statutory laws for prosecution. This study found that migrants who live with their employer are exposed to more severe forms of exploitation, humiliation, verbal abuse and sexual abuse at different stages of their migration process. The study argues that these migrant domestic workers’ stories provide further evidence that legal protections must be put in place for migrant domestic workers in South Africa.